STRATEGI PEMBERDAYAAN PETANI IKAN NILA (MERAH) BAGI PENINGKATAN EKONOMI MASYARAKAT - Sufi Sufi (Program Studi Administrasi Bisnis, 2021)
This study aims to determine and explain the empowerment of red tilapia fish farming for the young generation at Desa Penampaan Kecamatan Pokhkisen Southeast Aceh and the impact of empowering red tilapia fish farming for the younger generation and village income. The research method used is a qualitative method with data collection techniques using observation instruments, interviews and documentation. All data obtained are analyzed by means of reduction, then presented so that they are easily understood and conclusions can be found. The results of the study explained that; Empowering the cultivation of red tilapia for the younger generation at Desa Penampaan Kecamatan Pokhkisen Southeast Aceh through education and coaching and supplying seedlings and feed for the red tilapia fish farming business group for the younger generation where the source of funding comes from BUMK of Desa Penampaan Kecamatan Pokhkisen Southeast Aceh. The impact of empowering the cultivation of red tilapia for the younger generation and village income, namely for the younger generation who already have a job, already have the skills and expertise in maintaining the red tilapia and the young generation already has an income for their daily needs. While the impact for the village is that it can increase village assets and village income where profits derived from the harvest must be returned to the village treasury by 25% as original village income.